PENERAPAN SISTEM JAM DIGITAL PINTAR BERBASIS INTERNET OF THINGS UNTUK MENINGKATKAN EFISIENSI MANAJEMEN WAKTU DI SMA NEGERI 1 AIR JOMAN - Jhonson Efendi Hutagalung; Ari Dermawan; Junaidi Sholat (Smart Education, 2025)
Abstract: SMA Negeri 1 Air Joman faces problems of uncertainty and inconsistency in the school bell schedule due to the use of a manual system. This condition causes irregular learning times and decreases discipline among students and teachers. To address these issues, the implementation of a Smart Digital Clock System based on the Internet of Things (IoT) is proposed through a Community Service Program (PKM). The system is designed to automatically synchronize time via the internet, activate the school bell according to the programmed schedule, and display important information on an integrated LED screen.The program is carried out in four stages: partner needs analysis and survey, system design and development, installation and user training, and finally, evaluation of results. The expected outputs include the installation of one fully functional IoT-based digital clock system, improved technical skills of school staff, and enhanced discipline and punctuality in school activities.Through the implementation of this system, it is expected that an automated, accurate, and efficient school time management system will be realized, while also increasing technological literacy within SMA Negeri 1 Air Joman as a concrete step toward digital transformation in education. Keywords: Internet of Things, smart digital clock, school bell, discipline. Abstrak: SMA Negeri 1 Air Joman menghadapi permasalahan ketidakpastian dan ketidakkonsistenan jadwal bel sekolah akibat sistem manual yang masih digunakan. Kondisi ini menimbulkan ketidakteraturan waktu belajar dan menurunkan kedisiplinan siswa maupun guru. Untuk mengatasi hal tersebut, diusulkan penerapan Sistem Jam Digital Pintar berbasis Internet of Things (IoT) melalui program Pengabdian kepada Masyarakat (PKM). Sistem ini dirancang untuk menyinkronkan waktu otomatis melalui jaringan internet, mengaktifkan bel sesuai jadwal yang diprogram, dan menampilkan informasi penting pada layar LED terintegrasi. Kegiatan dilaksanakan melalui empat tahap, yaitu survei dan analisis kebutuhan mitra, perancangan dan pengembangan sistem, instalasi serta pelatihan penggunaan, dan evaluasi hasil. Target luaran meliputi pemasangan satu unit sistem jam digital berbasis IoT yang berfungsi penuh, peningkatan kemampuan teknis staf sekolah, serta peningkatan kedisiplinan dan ketepatan waktu kegiatan sekolah. Melalui penerapan sistem ini, diharapkan tercipta manajemen waktu sekolah yang otomatis, akurat, dan efisien sekaligus meningkatkan literasi teknologi di lingkungan SMA Negeri 1 Air Joman sebagai langkah nyata menuju transformasi digital di dunia pendidikan. Keywords: Internet of Things, Jam Digital Pintar, Bel Sekolah, Kedisiplinan.